Balancing act : the new medical ethics of medicine's new economics - Morreim, E. Haavi (Clinical medical ethics (Washington, D.C.), 1995)
In this volume, Dick Bryan examines the influence of the international economy upon domestic accumulation, describing the process as the expression of the contradiction between the international scope of accumulation and the national scope of its regulation. Developing a theoretical framework for understanding the contradiction within Marxist political economy, he addresses the theory of value on an international scale, as well as theories of global restructuring and crisis. These issues are then applied to those domestic policies - such as monetary policy and balance of payments - that interrelate with the international economy. The author argues that the conventional theories informing these approaches have consistently failed to recognize the contradictions in international accumulation. National economic management has, as a result, reverted to explicit class politics, attempting to solve domestic economic problems by targeting the living standards of labor.